2012
DOI: 10.1371/journal.pone.0033374
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Wolfberry Prevents Corticosterone-Induced Inhibition of Sexual Behavior and Increases Neurogenesis

Abstract: Lycium barbarum, commonly known as wolfberry, has been used as a traditional Chinese medicine for the treatment of infertility and sexual dysfunction. However, there is still a scarcity of experimental evidence to support the pro-sexual effect of wolfberry. The aim of this study is to determine the effect of Lycium barbarum polysaccharides (LBP) on male sexual behavior of rats. Here we report that oral feeding of LBP for 21 days significantly improved the male copulatory performance including increase of copul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Reports indicated Sildenafil, as a first-line medicine for treatment of erectile dysfunction and sexual dysfunction, increased sperm quantity and quality [29,51]. Our experiment showed similar findings, but the LBP showed a better reversal effect on the fertility impairment than sildenafil which might be caused by more mechanisms of action.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Reports indicated Sildenafil, as a first-line medicine for treatment of erectile dysfunction and sexual dysfunction, increased sperm quantity and quality [29,51]. Our experiment showed similar findings, but the LBP showed a better reversal effect on the fertility impairment than sildenafil which might be caused by more mechanisms of action.…”
Section: Discussionsupporting
confidence: 80%
“…As expected, an increase in the mean body weights was observed and this increase was statistically significant after administration of 40 mg/kg LBP, reflecting benefit of better blood glucose control. Previous studies showed that the improvement of the reduced testicular weights by the administration of LBP in animals might be attributed to the improvement of lesion of reproductive organs [33,39,40]. Recent studies utilized morphology based technique showed histopathological changes in the testis associated with DM [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LBP has hypoglycemic and hypolipidemic effects, and it could be used for treating type 2 diabetes [2] and cancer [3]. LBP improves sexual behavior and increases neurogenesis [4], as well as Alzheimer's disease (AD), colitis, fatigue, glaucoma and stroke [5].…”
Section: Introductionmentioning
confidence: 99%